Research, innovation and technological performance in Germany - EFI Report 2011 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2011)
In addition to discussing current trends and requirements for reform in the Federal Government's research and innovation policy, in its 2011 report the Commission focuses on four main points. In Chapter B 1, firstly, it discusses the tensions between Federal and Länder competencies in education, research and innovation policy. It calls for elimination of the prohibition on competition in education policy and for introduction of consistent distribution of responsibilities between the Federal Government and the Länder for financing of all nonuniversity research institutions. In Chapter B 2 the Expert Commission considers the European dimension of research and innovation, which has been gaining importance since 2000. It recommends that the Federal Government take a stronger role in the European co-ordination process – Germany must lead in the area of research and innovation, if it is to play a useful role in shaping the European Research Area. In Chapter B 3, the Expert Commission comments on the discussion relative to network neutrality. For the sake of innovation, it is vital that the Internet remains open in this regard – and the Expert Commission would like to see the Federal Government play a more active role on behalf of network neutrality. In Chapter B 4, the Expert Commission considers the still largely ignored role of those innovators who succeed even without undertaking research activities. Innovation processes do not conform to simple logical rules. Consequently, research and innovation policy concepts must be open, able to provide latitude for innovators without research and development (R&D) of their own. In its report, the Expert Commission again notes that the idea of introducing tax-based R&D support urgently needs to return to the political agenda. Similar priority needs to be given to providing a legal framework for business angels and venture-capital providers; such a framework is still lacking. Over the past few years, a good basis has been created for the development of Germany's research and innovation sector. But if lasting growth and prosperity are to assured in Germany, research and innovation in Germany will have to be additionally and substantially reinforced.,
Keywords: 330; Innovation; Forschung; Technischer Fortschritt; Deutschland